Comparison of Students' Mathematical Concept Understanding Ability in Polyhedron Material Using the Discovery Learning and Core Learning Model with The Assistance of Pop-Up Book Media - Inanda Shofa Azahroh; Fitria Zana Kumala (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
This research was motivated by the low ability of class VIII students at MTs N 1 Purbalingga to understand mathematical concepts. This research aims to compare students' ability to understand mathematical concepts in flat-sided geometric material using two different learning models, namely discovery learning and Connecting, Organizing, Reflecting, And Extending (CORE) with the help of pop-up book media. The research method used is quantitative with a quasi-experimental type of research. The population in this study were class VIII students at MTs N 1 Purbalingga for the 2022/2023 academic year. The sampling technique used simple random sampling, and the sample in this study were students in classes VIII D and VIII E, totaling 76 students. In experimental class I, I received teaching using the discovery learning model assisted by pop-up books. For experimental class II, I received teaching using the CORE model assisted by pop-up books. The data collection method uses tests in the form of pretest and posttest. The data analysis technique uses the n-gain and two independent samples t-tests. The research results showed that the average n-gain score in experimental class I was 0.656; in experimental class II, it was 0.366, which was in the medium category. Judging from the n-gain interpretation, the average percentage value obtained by experimental class I, namely 65.5%, is interpreted as quite effective. It is interpreted as ineffective in experimental class II, namely 36.6%. Based on analysis using the t-test for two independent samples, the significance value was 0.000 < α=0.05, so it can be concluded that there is a significant difference between the ability to understand mathematical concepts of students who use the pop-up book-assisted discovery learning model and the CORE assisted learning model on flat-sided building materials.